The Effect Of Special Exercises Using An Apparatus For Developing Muscular Strength, Special Endurance In Youth Soccer Players - Asaad, Mooafaq; Safoat, Ahmed (Journal of Physical Education, 2018)
The Effect Of Special Exercises Using An Apparatus For Developing Muscular Strength, Special Endurance In Youth Soccer Players The problem of the research lies in the weakness in the physical aspect that negatively affects physical performance of youth players in soccer. The importance of the research lies in designing an apparatus for developing lower extremities’ muscular strength as well as designing exercises to be performed on this apparatus. The researcher used the experimental method. The subjects were youth soccer players (2016 – 2017). The data was collected using SPSS to come up with the conclusions. The researchers concluded that there are significant statistical differences in muscular strength and endurance in youth soccer players understudy after using the apparatus and exercises. Finally they recommended using the apparatus for developing endurance, speed and strength in youth soccer players.